Manual de funciones para mejorar el desempeño laboral de los empleados de la clínica de especialidades Salud Card, del cantón Buena Fe provincia de Los Rios. - Canales Orobio, Leonor Dusmila (2012)
This study was made for the purpose of developing a functions manual for improving work performance of employees and workers of the Health Specialty Clinic-Card, located in the Streets Felipe Alvarez and Rodrigo Torres of canton Buena Fe, province of Rivers, for which it had the support of its owners, Dr. Fleishman Jimenez and Dr. Daly Barraza. To achieve the object of study were diagnosed with the current situation of human talent, established the organizational and functional structure of the clinic, which led to the design proposal of a Functions Manual. The study was just applying surveys to staff, interviews with the departmental head and shareholders of the clinic, the same which demonstrated that there are flaws in the operating and functional development of human talent, as a result of little knowledge, insufficient guidance and training of employees. It was determined that the current organizational structure is poorly defined and designed, therein are not all jobs, also has not created a working organizational chart specifying the charges according to the areas that currently owns the clinic. The documentary study is based on various themes and sub-themes, focused on the subject of study, particularly the manual functions. The information collected in this study strengthened knowledge of the investigator, also will guide the reader to understand the parameters and more important aspects of the research. In the methodological process used various types of research, fieldwork and documentary, which allowed removing through the application of methods, techniques and tools for evaluation, information concerning the object of study. The methodological model implemented in this study helped clear questions, objectives and verify the raised hypotheses, which made it possible to know the needs and shortcomings in the administrative and operational development of human talent in the clinic of specialties Salud-Card. The study allowed to verify the hypothesis raised "the elaboration of the manual of functions allows to determine the functions of the personnel that works in different areas of the clinic of specialties Salud-Card". The researcher and those involved in the present study rightly consider that the elaboration of a manual of functions will allow identifying the development of functions of the human talent in different areas of the clinic will also optimize the Labour Party and will prevent generation of shortcomings in the administrative processes - operatic. Deemed necessary to optimize the labor performance and organize human talent in the clinic, so need to socialize the proposal to the shareholders, administrative staff and collaborators, in showing where the manual functions, the new organizational and functional structure of the entity, is also important illustrate staff on the roles and responsibilities that this must meet job requirements. The manual functions proposed to be implemented will positively affect the operational development of human talent in the clinic of specialties Salud-Card, will instruct them in the development of their functions, will also allow you to make decisions right at the working level.